Bibliometric analysis of research trends and prospective directions of Akkermansia muciniphila from 2010 to 2024 - Wang, Yanan; He, Jiahui; Chen, Simin; Lv, Xinyi; Chen, Jiayi; Ru, Kaiyue; Liang, Xiao; Mao, Meng; Song, Yuehan (Frontiers in Microbiology, 2025)
BackgroundAkkermansia muciniphila (A. muciniphila) is an emerging probiotic with potential impact on human health, and there is a growing interest in this area, but an overall analysis of research trends is lacking. This study conducted a detailed bibliometric analysis and visualization of A. muciniphila research to examine the current research status, hotspots, and trends, aiming to inform future research directions.MethodsThis study utilized the Web of Science database to search research on A. muciniphila from 2010 to 2024. Bibliometric analysis was conducted using CiteSpace and VOSviewer software to generate yearly publication trends, contributions by countries, institutions, and distinguished researchers, as well as key themes and influential researches. This analysis aimed to visualize and explore the literature over the past 15 years, guiding future researches and identifying gaps in the field of intestinal flora in A. muciniphila.ResultsWe searched a total of 4,423 related publications. Wei Chen, Willem de Vos and Patrice D. Cani are the primary contributors to A. muciniphila ‘s research. The top contributing countries and institutions are China, the United States, South Korea, Spain, and Italy, with research centers such as the Chinese Academy of Sciences, Zhejiang University, the University of Copenhagen, and the University of Helsinki being the main contributors. Current research hotspots focus on the molecular biology of A. muciniphila, such as its role in intestinal barrier maintenance, immune response, and its potential for regulating and treating digestive and metabolic diseases, such as cancer, fatty liver disease, inflammatory bowel disease, etc., through bile acid metabolism, extracellular vesicles, and insulin resistance.ConclusionOur study synthesizes current research on A. muciniphila in various disease areas and suggests enhancing collaboration among countries, institutions, and authors to advance A. muciniphila—related clinical and basic research, explore its efficacy in a variety of diseases and the effects of commonly used clinical medications on A. muciniphila, to fill the research gaps in the current field, and to provide valid evidence for the development of A. muciniphila as a novel probiotic supplement.